IDENTIFIKASI DAN UJI AKTIVITAS SENYAWA FLAVONOID DARI EKSTRAK DAUN TREMBESI (Albizia saman (Jacq.) Merr) SEBAGAI ANTIBAKTERI Escherichia coli - I Kadek Pater Suteja; Wiwik Susanah Rita; I Wayan Gede Gunawan (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2016)
Identification of flavonoid from the leaves of rain tree (Albizia saman (Jacq.) Merr) and its antibacterial activity test against Escherichia coli (E.coli) has been performed. This research aims to determine the type of flavonoid in rain tree leaves and its antibacterial activity against E. coli. Extraction was done by maceration and partition methods, separation was achieved by column chromatography, antibacterial activity was tested by disk diffussion method, and the identification was done by Ultraviolet-visible (UV-vis) and Infrared spectrophotometry. Extraction of 1 kg of rain tree powder with 5 L ethanol produced 73.38 g of concentrated ethanol extract. The partition process produced 26,34 g of n-hexane, 8,12 g of ethylacetate, 19,37 g n-butanol, and 12,56 g of water extracts. Phytochemical test of the extracts showed that the n-butanol extract contained flavonoids. Antibacterial activity of n-butanol extract towards E.coli showed a medium activity with a diameter inhibition of 6.3 mm. MIC value ??was 2% (w/v) with a diameter inhibition of 1 mm. Separation using column chromatography with the eluent of n-butanol: methanol: chloroform (5: 3: 2) obtained four isolates but only one isolate (isolate B with Rf 0.58) which contained flavonoids. Analysis with infrared spectroscopy showed that the isolate B contained functional groups of OH, C-OH, aliphatic CH, C = O ketones, C = C aromatic, COC ether, and aromatic CH. Analysis with UV-Vis spectrophotometer indicated that isolate B is isoflavon compound with a hydroxy groups at C-5 and C-7. The isolate was relatively pure by TLC. The isolate showed a low antibacterial activity.